Drying Shrinkage of Slag Blended Fly Ash Geopolymer Concrete Cured at Room Temperature. (2015) - Deb, Partha Sarathi; Nath, Pradip; Sarker, Prabir Kumar
Abstract: Recent studies have shown that blending of ground granulated blast furnace slag (GGBFS) with low-calcium fly ash can have significant effects on the setting and early strength development of geopolymers cured at room temperature. This paper presents the shrinkage behaviour of geopolymer concrete mixtures in which class F fly ash was replaced with 10% or 20% GGBFS and the sodium silicate to sodium hydroxide (SS/SH) ratio was either 1.5 or 2.5. Shrinkage of 4 geopolymer and 1 ordinary Portland cement (OPC) concrete mixtures cured at room temperature were studied. Comparisons are made between the shrinkage behaviours of geopolymer concretes with different mixture proportions and those of the OPC concrete. It was found that shrinkage decreased with the increase of slag content and decrease of SS/SH ratio in geopolymer concrete cured at room temperature. The shrinkage of geopolymer concrete up to the age of 180 days was found to be comparable to that of OPC concrete of similar compressive strength. Thus, shrinkage of geopolymer concrete could be reduced to values within the limit recommended in the Australian Standards for normal OPC concrete.